Inhibition of the LKB1–AMPK pathway by the Epstein–Barr virus‐encoded LMP1 promotes proliferation and transformation of human nasopharyngeal epithelial cells. Issue 3 (7th June 2013) - Lo, Angela Kwok‐Fung; Lo, Kwok‐Wai; Ko, Chun‐Wai; Young, Lawrence S; Dawson, Christopher W
Abstract The association of Epstein–Barr virus (EBV) infection with the development of nasopharyngeal carcinoma (NPC) is well established. Latent membrane protein 1 (LMP1), the major oncogene encoded by EBV, is believed to play a crucial role in NPC pathogenesis by virtue of its ability to constitutively activate multiple cell signalling pathways. The LKB1–AMPK pathway is a master regulator of cellular metabolism that, via modulation of energy metabolism, has tumour suppressor activity. In this study we identify a novel ability of LMP1 to inhibit the LKB1–AMPK pathway through phosphorylation of LKB1 at serine 428 with subsequent suppression of the phosphorylation of AMPK and its substrates, ACC and Raptor. We show that MEK/ERK–MAPK signalling, activated by the CTAR1 domain of LMP1, is responsible for LKB1–AMPK inactivation. In addition, reactivation of AMPK signalling by AMPK activator, AICAR, abolished LMP1‐induced cellular transformation (proliferation and anchorage‐independent growth) in nasopharyngeal epithelial cells. Immunohistochemical staining revealed that a low level of phosphorylated AMPK is common in primary NPC specimens, and that this correlated significantly with the expression of LMP1. AICAR treatment inhibited the proliferation and anchorage‐independent growth of NPC cells as well as potentiating the cytotoxic effect of the chemotherapeutic drug 5‐fluorouracil. The current findings demonstrate that LMP1‐mediated AMPK inactivation contributes to the proliferation and transformation of epithelial cells, thereby implicating the LKB1–AMPK pathway in the EBV‐driven pathogenesis of NPC. Our findings also suggest that AMPK activators could be used to enhance the efficacy of conventional chemotherapeutic agents in the treatment of local and metastatic NPC. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.